MOLLY POLLY: PERMAINAN BERBASIS MEDIA PEMBELAJARAN UNTUK MENGEDUKASI ANTI PERILAKU PERUNDUNGAN - Nurul Habiba Makkatenni; Ancensius Tombo Bamba; Rahmatika Sidar Tandiallo; Nurmila Nurmila; Nadiah Ariqah (JURNAL PSIKOLOGI INSIGHT, 2021)
Abstract Bullying occupied the highest percentage as a case of violent children with the most case coverage in schools. The efforts to educate anti-bullying behavior need to be encouraged. One of them was by developing learning media. This research aimed to determine the effectiveness of Molly-Polly as game-based learning media to educate anti-bullying behavior in elementary school students. This research applied an experimental method by using one-group pre-test and post-test design. The intervention by Molly-Polly learning media was given to 144 students of elementary school which aged 7-12 years old who came from five schools in Makassar City. The data was obtained through respondents were analyzed by using paired sample t-tests. The result of the analysis showed a significant value of 0.000 less than 0.05. based on the research results, it can be concluded that the Molly-Polly learning media is effectively used to educate anti-bullying behavior in elementary school students. This research expected to be a scientific reference for education practitioner to educate anti-bullying behavior through Molly-Polly learning media.  Abstrak Kasus perundungan menempati persentase tertinggi sebagai kasus kekerasan pada anak dengan cakupan terbanyak terjadi di sekolah. Upaya mengedukasi perilaku anti perundungan perlu didorong, salah satunya dengan mengembangkan media pembelajaran. Penelitian ini bertujuan untuk mengetahui efektivitas media pembelajaran Molly-Polly sebagai upaya mengedukasi perilaku anti perundungan pada siswa sekolah dasar. Penelitian ini menggunakan metode intervensital dengan model one-group pre-test and pos-test design. Intervensi dengan media pembelajaran Molly-Polly diberikan kepada 144 siswa SD usia 7-12 tahun yang berasal dari lima sekolah dasar di Kota Makassar. Data yang diperoleh dari responden dianalisis dengan menggunakan uji-t sampel berpasangan. Hasil analisis menunjukkan nilai signifikan 0.000 kurang dari 0.05. berdasarkan hasil penelitian, dapat disimpulkan bahwa media pembelajaran Molly-Polly efektif digunakan untuk mengedukasi perilaku anti perundungan pada siswa sekolah dasar. Penelitian ini diharapkan dapat menjadi acuan ilmiah bagi para praktisi Pendidikan untuk mendidik perilaku anti perundungan melalui media pembelajaran Molly-Polly.